Radio Frequency Identification (RFID) Based Car Parking System - Muhammad Syamil Mazlan; Isredza Rahmi A Hamid; Hazalila Kamaludin (JOIV : International Journal on Informatics Visualization, 2018)
Radio Frequency Identification (RFID) technology is widely used in various applications such as attendance system, tracking system, monitoring system or parking system. Currently, the existing parking system used manual entrance through security guard to access the premise. Therefore, the company need to hire security guard to monitor the premise. In addition, the security guards need to monitor all movement of vehicle or person that enter or leave the premise. As a result, unauthorized vehicle or person can easily access the building. To address this problem, we proposed a parking system using RFID technology that can monitor vehicleâ€™s movement that enter or leave the specific area or place by scanning the RFID tag. The potential benefit is it can improve security for both security guards and users. Besides that, this parking system can facilitate access control for users and improve traffic flow during peaks period. There are five modules in the proposed parking systems which are user registration, vehicle registration, RFID tag, staff and report generation.Â